И. Е. Ворожейкин. Соревнование: от прошлого к настоящему - Сиволоб, Ю. В. (Український історичний журнал, 2025)
И. Е. Ворожейкин. Соревнование: от прошлого к настоящему. М.: Сов. Россия, 1990. — 224 с.